2011
DOI: 10.1111/j.1438-8677.2011.00448.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Arabidopsis solute carrier critical for intracellular transport and inter‐organ allocation of molybdate

Abstract: Plants represent an important source of molybdenum in the human diet. Recently, MOT1 has been identified as a transport protein responsible for molybdate import in Arabidopsis thaliana L.; however, the function of the homologous protein MOT2 has not been resolved. Interestingly, MOT2‐GFP analysis indicated a vacuolar location of this carrier protein. By site directed mutagenesis at the N‐terminal end of MOT2, we identified a di‐leucine motif that is essential for driving the protein into the vacuolar membrane.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
104
2
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(117 citation statements)
references
References 42 publications
7
104
2
3
Order By: Relevance
“…Additionally, di-Leu motifs in the N-terminal region of the monosaccharide transporter ERD SIX-LIKE1 (ESL1) (Yamada et al, 2010) and of the molybdate transporter MOT2 (Gasber et al, 2011) were shown to be responsible for the correct sorting of these transporters to the tonoplast.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, di-Leu motifs in the N-terminal region of the monosaccharide transporter ERD SIX-LIKE1 (ESL1) (Yamada et al, 2010) and of the molybdate transporter MOT2 (Gasber et al, 2011) were shown to be responsible for the correct sorting of these transporters to the tonoplast.…”
Section: Introductionmentioning
confidence: 99%
“…The latter is questionable, however, as the insertion of molybdenum into the Moco backbone takes place in the cytosol. For Mot2, GFP fusion proteins have been used to show that the protein localizes to the vacuolar membrane (17). Molybdate quantification in isolated vacuoles demonstrated that this organelle serves as an important molybdate storage compartment in Arabidopsis thaliana cells, where Mot2 was shown to be required for vacuolar molybdate export into the cytosol.…”
Section: Molybdenum Uptake Into Cellsmentioning
confidence: 99%
“…Molybdenum is one of the least abundant essential micronutrients in plants and soils, but it has critical roles in plant growth, nitrogen assimilation, and nitrogen-fixing symbiotic bacteroids (Kaiser et al 2005). Molybdenum is an essential element for nearly all organisms, necessary for Mo cofactor dependent enzymes including nitrate reductases, sulphite oxidase, xanthine oxidase, and dimethyl sulphoxide reductase (Schwarz et al 2009 (Gasper et al 2011) and another sulphate transporter from the nitrogen-fixing forage legume Stylosanthes hamata has also been shown to have some molybdate transporter activity (Fitzpatrick et al 2008). However, we were unable to identify MOT2 orthogenes in barley and the only known Mo-specific transporter likely to affect Mo assimilation is the MOT1 orthogene.…”
Section: Candidate Gene Assessmentmentioning
confidence: 97%